Nitrogen fertilization in rye (Secale cereale) used as a cover crop (Semiárida, 2020)
In order to evaluate the effect of nitrogen fertilization on rye used as cover crop (CC), under the hypothesis that aerial biomass production is conditioned by the availability of nitrogen in the soil, being the this influence significant on the Water Usage Efficiency (WUE), randomized block tests were established in four replications with the following treatments: fallow (B) without CC, unfertilized CC (T) and fertilized with 40 (40N), 80 (80N) and 120 kg N.ha-1 (120N). Soil moisture, N-NO3 - in soil (0 - 60 cm) and aerial biomass were determined with the aim of evaluating the incidence of different fertilization rates on dry matter (DM) production and WUE of rye used as CC, and to establish the productivity of the corn successor crop on the T and on the fertilized treatments. The results obtained in the 120N treatment were: CC DM production of 6447 kg.ha-1, WUE of 23 kg DM ha-1.mm-1, and corn production of 12170 kg.ha-1. While for the T treatment the DM production was 3815 kg.ha-1, the WUE was 13 kg DM.ha-1.mm-1, and the corn production was 9475 kg.ha-1, showing statistically significant differences between both treatments. The fertilization of the CC seems to be a viable alternative for the semi-arid Pampean Region as it has shown positive results in biomass production and in WUE. Corn crop productivity would be higher over fertilized CC compared to unfertilized CC. The decomposition of the CC residues could be responsible for the higher production, where the C/N relation plays an important role in the dynamics of degradation and in the supply synchronization of N in relation to the demand of the corn crop.Director: Quiroga, Alberto Raúl - Co Director: Fernández, Romina
Keywords: Semiarid region; Entisol; Soil nitrogen; WUE; Corn